(untitled) (Research, Society and Development, 2021)
Syphilis is an infectious disease of chronic evolution that affects several systems of the human body. Caused by the bacterium Treponema pallidum, a spirochete, which is mainly transmitted by unprotected sexual contact, blood transfusion and vertical transmission through the placenta. According to information from the Syphilis Epidemiological Bulletin, in 2019, 152,915 cases of acquired syphilis were registered across the country, with a detection rate of 72.8 cases per 100 thousand inhabitants. -natal to a syphilis patient, referring to the difficulties faced by nurses in the face of a syphilis diagnosis during pregnancy in scientific articles indexed in the electronic database of the BVS, LILACS, BDENF and SciElO, published between 2016 and 2020. it is a descriptive integrative review research with a qualitative approach, whose general objective will be to identify the behaviors performed by nurses in scientific platforms to minimize the impacts related to congenital syphilis. The results obtained allow us to obtain a broader view of the situation of gestational syphilis, contributing as an important source of data for epidemiological surveys carried out by health agencies and enabling them to direct their actions.